Safety and effectiveness of balloon cryoablation for treatment of Barrett’s associated neoplasia: systematic review and meta-analysis - Westerveld, Donevan R.; Nguyen, Khaai; Banerjee, Debdeep; Jacobs, Chelsea; Kadle, Nikhil; Draganov, Peter V.; Yang, Dennis (Endoscopy International Open, 2020)
Background and study aims Balloon cryoablation (BC) is a novel procedure for endoscopic ablation of Barrett’s esophagus (BE- associated neoplasia. We performed a meta-analysis to assess the feasibility, effectiveness, and safety of BC for treatment of BE neoplasia.Patients and methods Several databases were searched for relevant articles (PubMed, Web of Science, Google Scholar, EMBASE) as well as abstracts of recent gastroenterology meetings. Data extraction was performed by two investigators using standardized forms, including age, gender, length of BE segment, prior treatments, procedural time and number ablation sessions, technical feasibility, adverse events, and eradication rates of intestinal metaplasia (CE-IM) and dysplasia (CE-D) at follow-up. Quality of the studies was assessed using a modified Newcastle Ottawa Scale.Results Seven studies met inclusion criteria for a total of 548 ablation sessions in 272 patients. The most common histopathology reported prior to BC was high-grade dysplasia (n = 131), followed by low-grade dysplasia (n = 75), and intramucosal adenocarcinoma (n = 52). The pooled rate for technical feasibility was 95.8 % (95 % CI: 93.6–97.5 %; I2 = 13.2 %; P = 0.3). Pooled rates of CE-IM and CE-D were 85.8 % (95 % CI: 77.8–92.2 %, I2 = 55.5 %; p = 0.04) and 93.8 % (95 % CI: 85.5–98.7 %, I2 = 74.2 %; P = 0.001), respectively. The overall adverse event (AE) rate was 12.5 % (34 out of 272 patients), of which stricture formation was the most common (5.8 %), followed by mucosal laceration (0.7 %), perforation (0.4 %), and bleeding (0.4 %). All AEs were successfully managed endoscopically.Conclusion This meta-analysis suggests that BC is a safe and effective ablative technique for treatment of BE neoplasia; future prospective comparative trials are needed to corroborate these initial findings.